CREATIVE COMMUNITY DEVELOPMENT MODEL THROUGH ENVIRONMENT TECHNOLOGY, HEALTH BE-ING, ART AND DESIGN IN KHONKAEN - Thongdee, Witthaya; Promgun, Suraphon; Sawadtha, Suthipong; Namsithan, Somkhoun; Thubphumee, Panthiwa (Journal of Graduate MCU KhonKaen Campus, 2021)
The objectives of this research were 1) To study the enhancement of roles and functions of the KhonKaen community in driven force the smart city 2) To develop a creative community model through the process of technology, environment, health be-ing, art and design in KhonKaen The population of this study was 60 images / person. Specially randomized was used. Tools used as interviews and a specific group chat The data was analyzed using descriptive content analysis. The research results found that. 1) The process of enhancing community roles and functions depends on four important variables, which are: 1) Finding the reality is the cultivation of a consciousness to love the hometown. They are proud of their community. 2) Critical reflection It reflects the identity of KhonKaen people. Through equipment in the occupation. 3) Deciding on procedures for appropriate activities. Through activities, meetings, discussions, to find mutual agreements by participating in all parties and 4) maintaining effective practice. 2) The development of a creative community model through the process of technology, environment, health be-ing, art and design, KhonKaen City can be modeled as KIDPU model consisting of 1) K : Knowledge Management 2) I : Identity 3) D : Development 4) P : Publication 5) U: Utilization